Implementasi Peraturan Menteri Pendidikan dan Kebudayaan Nomor 64 Tahun 2015 tentang Kawasan Tanpa Rokok di Lingkungan Sekolah Sebagai Upaya Pencegahan Merokok pada Pelajar di SMP Kristen Atambua Kabupaten Belu - Murti Rana Bokamanu; Saryono Yohanes; Hernimus Ratu Udju (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The purpose of this study is to analyze the implementation of the Regulation of the Minister of Education and Culture Number 64 of 2015 concerning Smokefree Areas in the School Environment as an Effort to Prevent Smoking in Students at Atambua Christian High School, Belu Regency. This type of research shows empirical juridical research. The results of this study indicate that the implementation of the Regulation of the Minister of Education and Culture Number 64 of 2015 concerning Smokefree Areas in the School Environment is not / or has not been effective. There are several factors that influence the successful implementation of this regulation including legal structure, legal substance, and legal culture. These three factors certainly have an interest that always hinders or influences the implementation of rules regarding Smokefree Areas so as to make these rules ineffective. Based on the results of the study, the authors have several suggestions, namely increasing supervision of the implementation of the no smoking area policy in the school environment, ensuring law enforcement against violations of regulations consistently and firmly to create discipline in the school environment and conducting regular counseling and education programs to all students, teachers, and staff including school guards about smoking and the importance of a smoke-free environment.